Ius Constituendum on the Doctrine of Unlawful Nature in the Law on the Eradication of Corruption After the Constitutional Court Decision Number 003/PUU-IV/2006 - Nusa, Apriyanto; Zainuddin, Asriadi; Imran, Suwitno Yutye; Darmawati, Darmawati (JURNAL LEGALITAS, 2024)
The unlawful teachings in the explanation of Article 2 paragraph (1) of the Law on the Eradication of Corruption have been considered by the Constitutional Court as a norm that is contrary to the Constitution of the Republic of Indonesia in 1945, and does not have binding legal force. This condition has legal implications for the meaning of unlawful elements in Article 2 paragraph (1) of the Law on the Eradication of Corruption, becoming vague (vague norm). The purpose of this study is to analyze the unlawful teachings in the Law on the Eradication of Corruption in Ius Constituendum. This research uses normative legal research, which formulates the aspired law (ius constituendum) on the meaning of the element against the law (wederrechtelijkeheid) in the Corruption Eradication Law after the Constitutional Court Decision Number 003/PUU-IV/2006. The results of the discussion show that by assessing the basis of the Constitutional Court's legal considerations (ratio decidendi) Number 003/PUU-IV/2006. The cancellation of the explanation of Article 2 paragraph (1) of the Law on the Eradication of Corruption which adheres to the teachings of the nature of the act of violating formal and material laws, because it is considered that the concept of materiele wederechtelijk, which refers to unwritten law, is an uncertain measure.  The unlawful element in Article 2 paragraph (1) of the Law on the Eradication of Corruption Crimes is still interpreted as against formiele wedderechtelijkeheid and against materiele wedderecjhtelijkeheid in its negative function. As for its positive function, it must be considered contrary to the principle of protection and fair legal certainty regulated in Article 28D of the 1945 Constitution.